Comparison of the Ability of Two Brands of CBCT with That of SEM to Detect the Marginal Leakage of Class V Composite Resin Restorations - Mitra Karbasi Kheir; Leili Khayam (The Scientific World Journal)
Objectives. This study was carried out to compare the ability of two common brands of cone-beam computed tomography (CBCT), including New Tom and Planmeca, to detect the marginal leakage of class V composite resins. The ability of each of the two brands of CBCT to detect the marginal leakage of class V composite resins was also compared with that of scanning electron microscopy (SEM). Methods. Class V cavities were prepared on the buccal surface of sixteen extracted caries-free human premolars. Cavities were conditioned and filled with composite resin. The teeth were immersed in 50% weight/weight aqueous silver nitrate solution for 24 hours. They were then taken out and rinsed with distilled water. Next, they were put in a developing solution. They were first viewed with New Tom and Planmeca CBCT units and were then sectioned and evaluated by an SEM. Results. The results of the Wilcoxon signed-rank test showed no significant difference between the mean marginal leakage scores of New Tom and Planmeca CBCT images (p value = 0.157) and between those of New Tom CBCT and SEM images (p value = 0.098). However, there was a significant difference between the mean marginal leakage scores of Planmeca CBCT and SEM images (p value = 0.023). Conclusion. There were no significant differences between New Tom and Planmeca CBCT units in the detection of marginal leakage of class V composite resins. However, when these CBCT units were compared with the SEM, the New Tom CBCT unit could detect the marginal leakage better than Planmeca.